Morfologia dos esporos de pteridófitas amazônicas (Typus). - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1971)
The authors studied the morphology of the spores of 12 Typus of Pteridophyta from Amazonian Region, belonging to the Herbarium of Museu Paraense Emílio Goeldi. The observations and measures were realized with acetholized material.
Keywords: Morfologia; Pteridófitas; Morphology; Pteridophyta; Amazônia